Lactate clearance as a predictor of mortality in neonatal sepsis - Felix Nathan Trisnadi; Ekawaty Lutfia Haksari; Tunjung Wibowo (Indonesian Pediatric Society, 2016)
Background Neonatal sepsis remains the leading cause of neonatal deaths. Therefore, efforts should be made to reduce its mortality. Lactate clearance can be used as a marker of onset of hypoxia and microcirculation disorders, as well as to predict patient outcomes.Objective To assess the use of lactate clearance to predict mortality from neonatal sepsis.Methods We conducted a prospective cohort study in the levels 2 and 3 of neonatal care unit, Department of Child Health, Dr. Sardjito General Hospital, Yogyakarta, from October to November 2011. We enrolled 40 neonatal sepsis patients, who were divided into either the high or low lactate clearance groups. All neonates were followed up until they were discharged from the hospital, as to whether they survived or died. We performed blood lactate measurements early on following their diagnosis of sepsis, and after the subsequent six hours following the first antibiotic administration. Logistic regression for the multivariate analysis and ROC curves for the accurate analysis of predictive outcome factors were performed.Results More deaths occurred in neonates with low lactate clearance at six hours (48%) than in those in the high lactate clearance group (7%). Low lactate clearance at six hours was a significant predictor of mortality (RR 15.1; 95%CI 1.7 to 133), whereas the ROC analysis showed moderate accuracy.Conclusion Lactate clearance at six hours may be used as a predictor of mortality in infants with neonatal sepsis.